(untitled) (Педагогіка вищої та середньої школи, 2008)
Capabilities of the course “Pedagogy and Psychology ” in the development of humanistic orientation of teachers to be are developed and substantiated in the article. The most effective methods, forms of organization and means of teaching and upbringing aimed at training of modern humanist teachers are considered.